Harnessing the power of health taxes. (18th June 2020) - Jain, Vageesh; Baker, Peter; Chalkidou, Kalipso
Abstract : Health taxes are a cost effective opportunity for progress in public health. Yet decision making processes on such policies lack the diligence routinely used in appraising other health interventions, and this limits their use, say Vageesh Jain and colleagues